Diverse perspectives on action for positive social and environmental change. Issue 2 (1st February 2020) - Derr, Victoria
Abstract: This article presents an exploration of diverse adults' motivations for action to promote social and environmental change at a California public university. Semi-structured interviews with current or graduated university students reveal how they navigate their own identities and intersectionalities in developing an activist orientation and their views on collective action. Significant contributing factors in sustaining action include experiences that allowed participants to experiment with and learn from action, and settings in which participants see themselves as part of a community. This research contributes to an understanding of how diverse individuals develop commitment to social and environmental action with implications for environmental education practice.